Perseverance in the parish?: religious attitudes from a Black Catholic perspective - Davis, Darren W. (Cambridge studies in social theory, religion, and politics, 2017)
African American Catholics, though small in number and historically the targets of racial intolerance, are now the backbone of the church. The vast majority of African American Catholics do not perceive racial marginalization and intolerance in the church. African American Catholics are among the strongest religious identifiers in the church, while whites show a more fragile Catholic identity. The Catholic church may have finally overcome its racist past for the vast majority of African American Catholics, but serious concerns remain for white Catholics. Based on data from a national religion survey, this book explores religious attitudes from an African American Catholic perspective.